1976
DOI: 10.1152/ajplegacy.1976.230.5.1354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to stroke in spontaneously hypertensive rats

Abstract: Hypertension and stroke in spontaneously hypertensive rats (SHR) were investigated genetically using stroke-prone SHR (A3), stroke-resistant SHR (C) and their hybrids, hybrid of A3 and C (F1), offspring of F1 X F1 (F2), and those of backcrossing of F1 to the respective parental strains, BC(F1 X A3) and BC(F1 X C). The average blood pressure measured without anesthesia increased in the following order during the experimental period: C less than BC (F1 X C) less than F1 approximately F2 less than BC(F1 X A3) les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 0 publications
0
88
0
Order By: Relevance
“…Animals were placed on a Japanese style diet (Laboratorio Dott. Piccioni, Gessate, Italy; 18.7% protein, 0.37% sodium, 0.63% potassium) and received 1% NaCl in their drinking water starting at 6 wk of age (13). In our laboratory, the occurrence of cerebrovascular accidents, as documented by unequivocal physical signs (paralysis of at least one limb) and histological evidence, is observed in the SHRSP strain under these experimental conditions between 6 and 12 wk after initiating the dietary regimen described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were placed on a Japanese style diet (Laboratorio Dott. Piccioni, Gessate, Italy; 18.7% protein, 0.37% sodium, 0.63% potassium) and received 1% NaCl in their drinking water starting at 6 wk of age (13). In our laboratory, the occurrence of cerebrovascular accidents, as documented by unequivocal physical signs (paralysis of at least one limb) and histological evidence, is observed in the SHRSP strain under these experimental conditions between 6 and 12 wk after initiating the dietary regimen described above.…”
Section: Methodsmentioning
confidence: 99%
“…The occurrence of stroke in this strain has been recognized as a complex, multifactorial phenomenon in which specific ecogenetic interactions play a decisive role: both elevated blood pressure (9) and a specific dietary regimen (10) (the "Japanese" rat chow, which is higher in sodium, and lower in potassium and protein than Western diets) (11) are essential permissive elements to produce the stroke-prone phenotype. If these conditions are met, SHRSP show an extremely high rate of stroke which occurs rapidly within a few weeks to months (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…SHRSP develop severe nephrosclerosis and hypertensioninduced renal injury as well 2,7 . SHRSP also exhibit behavioral abnormalities including increased ambulatory activity and disrupted circadian rhythms; these behavioral abnormalities are considered to correspond to the delirium state observed in patients with dementia after cerebrovascular accidents 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PBN does not adversely affect the taste of drinking [18]. Stroke-onset was assessed by the appearance of neurological symptoms such as hypokinetic/hyperkinetic syndrome and limb paralysis, and changes in body weight, water intake and circadian rhythm disturbances in HR, blood pressures and locomotive activity [3,4].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…M-SHRSP serves as a suitable model of hypertension-induced cerebrovascular stroke due to the spontaneous development of stroke at a relatively early age (approximately 80 days) without any need for salt-loading. Stroke-onset in SHRSP has been assessed using neurological signs (behavior), body weight loss, and marked increases in water intake, corroborated by the presence of brain lesions at autopsy [3]. Tabuchi et al recently showed disturbance of circadian rhythms in heart rate (HR), diastolic blood pressure (DBP), systolic blood pressure (SBP) and locomotive activity using a telemetric system [4].…”
Section: Introductionmentioning
confidence: 99%